Evaluation of oral care protocols practice by dentists in Rio de Janeiro towards HIV/AIDS individuals - Carina Maciel Silva-Boghossian; Brenda Azzariti Berrondo Boscardini; Claudia Maria Pereira; Edson Jorge Lima Moreira (BMC, 2020)
Abstract Background The aim of this study was to evaluate the dentists' knowledge and practice regarding HIV positive individuals' oral care in Rio de Janeiro State. Methods Dentists from Rio de Janeiro State (n = 242) answered an electronic questionnaire on biosafety procedures, oral manifestations of AIDS, and knowledge of HIV infection. Collected information was stratified by gender, and data were analyzed using Chi-square and t tests. Results From the 14 oral manifestations investigated, oral candidiasis, necrotizing ulcerative gingivitis, and hairy leucoplakia were more associated with HIV, with no differences between the responses from men and women. Above 85% of the participants would be concerned about becoming infected with HIV after a needle/ sharp object injury and more than 80% of them were willing to be tested for HIV. However, significantly more women (98.8%), compared to men (91.3%), said they knew that HIV/ AIDS patients can contaminate dental care professionals, p = 0.007. There was a significant difference in the answers for the questions: "Are there special dental clinics for treatment of HIV/AIDS patients in Brazil?" (p = 0.044), and "Do the negative HIV tests surely indicate that the persons are free of viruses?" (p = 0.005). Significant differences between men and women were also observed regarding use of disposable mask (p = 0.01), and cap (p < 0.0001). Conclusion Most dentists who participated in the study presented a good knowledge on the care of HIV/ AIDS individuals, including biosafety protocols and in terms of the oral manifestations commonly associated to AIDS.